Minimal adjuvant chemotherapy for children with hepatoblastoma resected at diagnosis (AHEP0731): a Children’s Oncology Group, multicentre, phase 3 trial - Katzenstein, Howard M (Lancet Oncol, 2019)
BACKGROUND: Hepatoblastoma treatment with curative intent requires surgical resection, but only about a third of newly diagnosed patients with hepatoblastoma have resectable disease at diagnosis. Patients who have upfront resection typically receive a total of 4–6 cycles of adjuvant chemotherapy post-surgery, with the combination of cisplatin, fluorouracil, and vincristine. We aimed to investigate whether event-free survival in children with hepatoblastoma who had complete resection at diagnosis could be maintained with two cycles of adjuvant chemotherapy. METHODS: In this Children’s Oncology Group, multicentre, phase 3 trial, patients were enrolled in four risk groups on the basis of Evans surgical stage, tumour histology, and levels of α-fetoprotein at diagnosis to receive risk-adapted therapy. Here, we report on the low-risk stratum of the trial. Eligible patients were younger than 21 years and had histologically confirmed, stage I or II hepatoblastoma without 100% pure fetal stage I or small-cell undifferentiated histology; elevated serum α-fetoprotein level (>100 ng/mL); a complete resection at diagnosis; at least 50% Karnofsky (patients >16 years) or Lansky (patients ≤16 years) performance status; and had received no previous chemotherapy or other hepatoblastoma-directed therapy. Patients received two 21-day cycles of cisplatin, fluorouracil, and vincristine within 42 days of resection, consisting of cisplatin (100 mg/m(2) per dose or 3·3 mg/kg per dose for children <10 kg) intravenously over 6 h on day 1; fluorouracil (600 mg/m(2) per dose or 20 mg/kg per dose for children <10 kg) intravenous push on day 2; and vincristine (1·5 mg/m(2) per day to a maximum dose of 2 mg, or 0·05 mg/kg per day for children <10 kg) intravenous push on days 2, 9, and 16. The primary outcome was investigator-assessed event-free survival. As prespecified by protocol, we analysed the primary endpoint 6 years after enrolment (cutoff date Dec 31, 2017). This trial is registered with ClinicalTrials.gov, number ClinicalTrials.gov NCT00980460, and is now permanently closed to accrual. FINDINGS: Between May 18, 2010, and May 28, 2014, 51 patients in 32 centres in two countries were enrolled into the low-risk stratum of this trial, of whom 49 received c hemotherapy treatment after surgery and were evaluable for activity and safety. Median follow-up time for all evaluable patients was 42 months (IQR 36–62). 4-year event-free survival was 92% (95% CI 79–97) and 5-year event-free survival was 88% (72–95). Two (4%) of 49 patients had surgical complications (bile leaks). The most common grade 3–4 adverse events were febrile neutropenia in seven (14%) patients, decreased neutrophil count in three (6%) patients, infections in four (8%) patients, and diarrhoea in four (8%) patients. Ototoxicity occurred in one (2%) patient. One (2%) patient of the three who relapsed in this cohort died from disease. Two (4%) patients died in clinical remission after therapy discontinuation. One patient died of pneumonia and bacterial sepsis 1 year after therapy discontinuation and another patient died of unrelated causes 57 months after therapy completion. There were no treatment-related deaths. INTERPRETATION: Minimal postoperative chemotherapy with two cycles of cisplatin, fluorouracil, and vincristine can ensure disease control in patients with hepatoblastoma resected at diagnosis. Our results show that dose reduction of ototoxic agents is a safe, effective treatment for these children.